A concise flow synthesis of indole-3-carboxylic ester and its derivatisation to an auxin mimic - Baumann, Marcus; Baxendale, Ian R.; Deplante, Fabien (Beilstein Journal of Organic Chemistry, 2017)
An assembled suite of flow-based transformations have been used to rapidly scale-up the production of a novel auxin mimic-based herbicide which was required for preliminary field trials. The overall synthetic approach and optimisation studies are described along with a full description of the final reactor configurations employed for the synthesis as well as the downstream processing of the reaction streams.
Keywords: flow chemistry; heterocycle; hydrogenation; indole; multistep

(untitled) - Kaushik, N. K.; Kaushik, N.; Attri, P.; Kumar, N.; Kim, C. H.; Verma, A. K.; Choi, E. H. (Molecules, 2013)

Heterocyclic Scaffolds II: Reactions and Applications of Indoles - Gribble, G. W. (Springer, 2010)

The Alkaloids. Chemistry and Biology - Knölker, H.-J. (Academic Press, 2014)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N. (Beilstein J. Org. Chem., 2011)

(untitled) - Ferro, N.; Bredow, T.; Jacobsen, H.-J.; Reinard, T. (Chem. Rev., 2010)

(untitled) - Fischer, E.; Jourdan, F. (Ber. Dtsch. Chem. Ges., 1883)

(untitled) - Taber, D. F.; Tirunahari, P. K. (Tetrahedron, 2011)

(untitled) - Stazi, F.; Maton, W.; Castoldi, D.; Westerduin, P.; Curcuruto, O.; Bacchi, S. (Synthesis, 2010)

(untitled) - Kitching, M. O.; Dixon, O. E.; Baumann, M.; Baxendale, I. R. (Eur. J. Org. Chem., 2017)

(untitled) - Assmann, N.; Ładosz, A.; von Rohr, P. R. (Chem. Eng. Technol., 2013)

(untitled) - Filipponi, P.; Gioiello, A.; Baxendale, I. R. (Org. Process Res. Dev., 2016)

(untitled) - Filipponi, P.; Baxendale, I. R. (Eur. J. Org. Chem., 2016)

(untitled) - Browne, D. L.; Deadman, B. J.; Ashe, R.; Baxendale, I. R.; Ley, S. V. (Org. Process Res. Dev., 2011)

(untitled) - Hu, D. X.; O’Brien, M.; Ley, S. V. (Org. Lett., 2012)

(untitled) - Fitzpatrick, D. E.; Ley, S. V. (React. Chem. Eng., 2016)

(untitled) - Bryan, M. C.; Wernick, D.; Hein, C. D.; Petersen, J. V.; Eschelbach, J. W.; Doherty, E. M. (Beilstein J. Org. Chem., 2011)

(untitled) - Jones, R. V.; Godorhazy, L.; Varga, N.; Szalay, D.; Urge, L.; Darvas, F. (J. Comb. Chem., 2006)

(untitled) - Belley, M.; Sauer, E.; Beaudoin, D.; Duspara, P.; Trimble, L. A.; Dubé, P. (Tetrahedron Lett., 2006)

(untitled) - Belley, M.; Scheigetz, J.; Dubé, P.; Dolman, S. (Synlett, 2001)

(untitled) - Walkington, A.; Gray, M.; Hossner, F.; Kitteringham, J.; Voyle, M. (Synth. Commun., 2003)

(untitled) - Xing, R.; Tian, Q.; Liu, Q.; Li, L. (Chin. J. Chem., 2013)

(untitled) - Choi, I.; Chung, H.; Park, J. W.; Chung, Y. K. (Org. Lett., 2016)

(untitled) - Kalir, A.; Pelah, Z. (Isr. J. Chem., 1966)

(untitled) - Munshi, K. L.; Kohl, H.; De Souza, N. J. (J. Heterocycl. Chem., 1977)

WO Patent - Bensen, D.; Finn, J.; Lee, S. J.; Chen, Z.; Lam, T. T.; Li, X.; Trzoss, M.; Jung, M.; Nguyen, T. B.; Lightsone, F.; Tari, L. W.; Zhang, J.; et al. (Tricylic gyrase inhibitors, 2012)

(untitled) - Raucher, S.; Koolpe, G. A. (J. Org. Chem., 1983)

(untitled) - Tischler, A. N.; Lanza, T. J. (Tetrahedron Lett., 1986)

(untitled) - Farghaly, A.-R.; Haider, N.; Lee, D.-H. (J. Heterocycl. Chem., 2012)

(untitled) - Zhang, M.-Z.; Mulholland, N.; Beattie, D.; Irwin, D.; Gu, Y.-C.; Chen, Q.; Yang, G.-F.; Clough, J. (Eur. J. Med. Chem., 2013)

(untitled) - Yamada, N.; Kataoka, Y.; Nagaami, T.; Hong, S.; Kawai, S.; Kuwano, E. (J. Pestic. Sci. (Tokyo, Jpn.), 2004)

(untitled) - Kumar, D.; Vemula, S. R.; Cook, G. R. (Green Chem., 2015)

(untitled) - Zampieri, D.; Mamolo, M. G.; Laurini, E.; Fermeglia, M.; Posocco, P.; Pricl, S.; Banfi, E.; Scialino, G.; Vio, L. (Bioorg. Med. Chem., 2009)

(untitled) - Jansen, M.; Rabe, H.; Strehle, A.; Dieler, S.; Debus, F.; Dannhardt, G.; Akabas, M. H.; Lüddens, H. (J. Med. Chem., 2008)

(untitled) - Mallia, C. J.; Baxendale, I. R. (Org. Process Res. Dev., 2016)

(untitled) - Cossar, P. J.; Hizartzidis, L.; Simone, M. I.; McCluskey, A.; Gordon, C. P. (Org. Biomol. Chem., 2015)

(untitled) - Konishi, K.-i.; Nishiguchi, I.; Hirashima, T. (Chem. Express, 1986)

(untitled) - Yang, X.; Fu, H.; Qiao, R.; Jiang, Y.; Zhao, Y. (Adv. Synth. Catal., 2010)